Application of Sitting and Lying Diabetic Leg Exercises with a Decrease Blood Sugar Levels on Diabetes Mellitus Type 2 Patients - Heri, Heri; Muda, Iskandar; Khumaidi, Khumaidi; Sukmana, Mayusef (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Introduction: diabetes mellitus is a disease characterized by increased blood sugar levels. Blood sugar levels, if not controlled, will cause severe body system dysfunction. Diabetes mellitus has management in the form of physical exercise. The recommended exercise is diabetic foot exercise. Methods: This study used a descriptive research design with a case study approach carried out in March 2023 with two respondents in the Sidomulyo Health Center area using SOP for diabetic foot exercises. Results: The blood sugar levels results before being given therapy on the first day; R1=227 and R2=213. On the second day, R1=219 and R2=203. On the third day, R1=236 and R2=195. On the fourth day, R1=226 and R2=192. After being given therapy on the first day, R1=208 and R2=194. On the second day, R1=210 and R2=171. On the third day, R1=212 and R2=166. On the fourth day, R1=200 and R2=164. Conclusion: There is a decrease in type 2 diabetes mellitus patients after being given diabetic leg exercises while sitting and lying down.Keywords: Diabetic Foot Exercise, Blood Sugar Levels, Type 2 Diabetes Mellitus